Determinants of Knowledge Workers Retention - Useng, Nursahida (วารสารวิทยบริการ มหาวิทยาลัยสงขลานครินทร์ | Academic Services Journal, Prince of Songkla University; Vol 28 No 3 (2560): Academic Services Journal, Prince of Songkla UniversityDO - 10.14456/asj-psu.2017.56, 2017)
In the modern environment, knowledge worker retention has been described as the most reliable means of ensuring sustainable competitive advantage. On that ground, understanding how to retain knowledge worker has become an inevitable process for companies. Strategic human resource management must be in place and closely involved in every stages during the tenure of employment. It is the best practice for management to recognize who are the knowledge workers inside the organization and to be well-planned for them, thus they will not be burnt out and leave the company. On the other hand, it will create awareness for them to continuously retain in current employment. The importance of retaining knowledge worker was formed into the context of this documentary research. In terms of analysing factors that influences retention level of knowledge worker. It was found from the previous studies that employees’ decision to stay with any given company is reflected on four importance factors which are career development opportunities, recognition and value at work, relationships with supervisor and co-worker, and, salary/bonus/incentive/reward. Positive aspects of these factors will influence their loyalty positively, which will influence overall retention positively. This article will contribute to provide the strategy recommendation of knowledge worker retention to organization. It can be applied to prevent the lose in organization in term of financial and non-financial due to high turnover of knowledge worker. Human resource personnel and supervisors may apply the best practice as recommended in this paper to retain the knowledge worker with current organization. Keywords: knowledge worker, employee retention, sustainable competitive advantage